Stability of Waste Dumps at Kennecott's Bingham Canyon Mine - A. D. Pernichele; M. B. Kahle (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1972)
Four types of slope failures in waste dumps are recognized debris flow, foundation failure, edge slump, and blowout. The first three types, although at times causing considerable damage to property and interfering with mine operations, are not usually dangerous to personnel because of their slow rate of movement. The fourth type, the blowout, is the most dangerous because of its explosive mode of failure and lack of forewarning. The December 1969 failure at Verona dump is presented as an example of a blowout. Data from piezometer holes indicate that the blowout was due to perched leach solutions near the face of the dump. The level of water in this zone is very closely related to the rate of leach water application on the dump. A detailed analysis of core samples indicates that the impounded water was perched on a zonal accumulation of jarosite which is associated with a buried dump surface. Drain holes proved successful in controlling perched leach solutions in the critical zone near the face of the dump. Monitoring of the water level in the perched zone is considered essential in preventing blowouts. The use of drain and piezometer holes has allowed an increase in the rate of water application on the dump while preventing additional failure.